2016
DOI: 10.1111/ped.12898
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual maturity and physical fitness in preschool children

Abstract: From an early age, physical-motor performance and intellectual maturity are linked. Fitness condition is able to predict intellectual maturity. Increasing the amount of time devoted to physical education can promote cognitive benefits in preschool children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
1
14
0
6
Order By: Relevance
“…Besides the well‐described association between PF with a cluster of metabolic risk factors in children, adolescents, and adults (Ruiz et al., ; Ortega et al., ; Kvaavik et al., ; Zagout et al., ), there is increasing evidence of an association between PF and academic performance (AP) (Grissom, ; Chomitz et al., ). This could be due to PF's positive effects on cognitive function and performance in attention tasks, or by its effects on depression, stress, and sleep quality (Blumenthal et al., ; Chang & Chen, ; Latorre et al., ). Cognition and motor skills in children have several common underlying processes, such as sequencing, monitoring, and planning which may positively influence AP (Roebers & Kauer, ; Van der Fels et al., ).…”
mentioning
confidence: 99%
“…Besides the well‐described association between PF with a cluster of metabolic risk factors in children, adolescents, and adults (Ruiz et al., ; Ortega et al., ; Kvaavik et al., ; Zagout et al., ), there is increasing evidence of an association between PF and academic performance (AP) (Grissom, ; Chomitz et al., ). This could be due to PF's positive effects on cognitive function and performance in attention tasks, or by its effects on depression, stress, and sleep quality (Blumenthal et al., ; Chang & Chen, ; Latorre et al., ). Cognition and motor skills in children have several common underlying processes, such as sequencing, monitoring, and planning which may positively influence AP (Roebers & Kauer, ; Van der Fels et al., ).…”
mentioning
confidence: 99%
“…In this sense and taking into account the third objective of the current study, to analyses the relationship between the CGT and cognitive measures; we found a significant correlation between the CGT with PMT and GHDT. Likewise, previous studies have shown that higher performance in physical fitness and motor skills in preschoolers seems to be related to improved spatial working memory and/or attention (Niederer et al, 2009) and intellectual maturity (measured by the GHDT) (Latorre-Román et al, 2016;Tanaka, 2006). In this sense, in accordance with Niederer et al, (2009) in the cross-sectional analyses, agility, tested through the CGT, is most consistently related to both cognitive measures, because this kind of resource-demanding tests involves both physical and cognitive resources.…”
Section: Discussionmentioning
confidence: 82%
“…The mastery of FMS contributes to children's physical, cognitive, and social development and is essential for an active lifestyle (Lubans, Morgan, Cliff, Barnett, & Okely, 2010). The presence of sex differences in FMS and physical fitness has been largely agreed upon (Foulkes et al, 2015;Latorre-Román, Mora-López, & García-Pinillos, 2016;Morris, Williams, Atwater, & Wilmore, 1982); although boys exceeded on some measures and girls on others, these differences may not be uniform throughout the whole preschool period when analyzing by age; and currently, the literature is inconclusive about the differences between the sexes in FMS (Kokštejn, Musálek, & Tufano, 2017). Therefore, a wide range of individual differences in motor-skill development is likely present between different ages and sexes (Kokštejn, Musálek, & Tufano, 2018).…”
mentioning
confidence: 99%
“…Los resultados de este estudio indican que la práctica de natación constituye una actividad deportiva de gran interés para esta población, pues contribuye a estimular el desarrollo de dos reconocidos componentes fundamentales de la condición física saludable en prescolares, como son la resistencia y la fuerza (Ayán-Pérez, Cancela-Carral, Lago-Ballesteros, & Martínez-Lemos, 2017;Ayán, Cancela, Romero, & Alonso, 2015). Es más, algunos autores han sugerido que el estimular la condición física a estas edades podría traducirse en mejoras en la función cognitiva (Latorre et al, 2016), aspecto que resalta todavía más los beneficios potenciales que se podrían derivar de participar en programas de iniciación a la natación como el aquí descrito.…”
Section: Discussionunclassified